2018
DOI: 10.1172/jci93561
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensing and fibrosis

Abstract: Tissue injury disrupts the mechanical homeostasis that underlies normal tissue architecture and function. The failure to resolve injury and restore homeostasis gives rise to progressive fibrosis that is accompanied by persistent alterations in the mechanical environment as a consequence of pathological matrix deposition and stiffening. This Review focuses on our rapidly growing understanding of the molecular mechanisms linking the altered mechanical environment in injury, repair, and fibrosis to cellular activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
191
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(193 citation statements)
references
References 205 publications
(202 reference statements)
2
191
0
Order By: Relevance
“…Liver disease progression is strongly associated with abnormal tissue architecture and mechanotransduction 15,34,35 . Indeed, as a direct effect of aberrant ECM deposition in the fibrotic liver, tissue stiffness increases in time and severely compromises its function [36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…Liver disease progression is strongly associated with abnormal tissue architecture and mechanotransduction 15,34,35 . Indeed, as a direct effect of aberrant ECM deposition in the fibrotic liver, tissue stiffness increases in time and severely compromises its function [36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…Matrix stiffness, clinically viewed as the end‐stage of organ fibrosis, gradually occurs during the development of tissue fibrosis and increases remarkably in line with deposition, cross‐linking, and reconstruction of the matrix . Recent advances have demonstrated that matrix stiffness has a pivotal role both as the cause and outcome of fibroblast activation in pathological fibrosis . Therefore, targeting the matrix to control tissue repair and fibrosis could be considered as a potential therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The fibrotic ECM increases organ stiffness. This rigidity perpetuates disease progression 4,5 . Despite renal fibrosis being a significant contributor to patient morbidity and mortality there are no anti-fibrotic drugs currently approved.…”
Section: Introductionmentioning
confidence: 99%
“…Fibrotic ECM signals via cell-surface integrins to control the cytoskeletal and mechanical properties of myofibroblasts 4,6 . Previously, we identified cytoskeletal alterations in liver myofibroblasts, downstream of integrin ÎČ1, mediated through actomyosin signaling via P21-activated kinase (PAK1) and the mechanical transcriptional effector, Yes-associated protein 1 (YAP1) 7,8 .…”
Section: Introductionmentioning
confidence: 99%